DIPLOMASI MARITIM INDONESIA DI IORA PADA KASUS ILLEGAL, UNREPORTED, DAN UNREGULATED FISHING - Hino Samuel Jose; Laode Muhamad Fathun (Universitas Jenderal Ahmad Yani, 2021)
Maritime sovereignty is an integral part of the Indonesia’s foreign policy, historically in the era of Nusantara, many competitions to conquer maritime territory was even tangible from the era of Majapahit and Sriwijaya kingdom during their ruling. With the notion of Indonesia as the world’s maritime axis, Indonesia’s diplomacy is defined clearly by the manifestation of efforts either in bilateral, regional, and multilateral. This article discussed on how Indonesia’s diplomacy through IORA cooperation is done to overcome the issue of IUU fishing during the presidency of Joko Widodo from 2015 until 2020. Indonesia’s IORA Chairmanship from 2015-2017 has rejuvenate Jakarta’s maritime diplomacy. Indonesia’s diplomacy depicted that Indonesia is beyond thatn norm-setting but also to the level where Indonesia assert their identity as a sovereign maritime axis amid the challenges and modernization that made non-traditional security as one of the core of contemporary diplomacy.